2003
DOI: 10.1258/jrsm.96.3.122
|View full text |Cite
|
Sign up to set email alerts
|

Cause and outcome of atypical chest pain in patients admitted to hospital

Abstract: SUMMARYIn patients with acute chest pain the prime need, usually, is to diagnose and treat myocardial infarction or ischaemia. When a cardiac origin for the pain has been excluded, patients are commonly discharged without either a diagnosis or a plan for follow-up. We studied a group of such patients to see how far causation was pursued and how their mortality compared with that of patients with a proven cardiac cause for their symptoms. The study population was 250 patients admitted over five weeks with chest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 12 publications
3
41
1
6
Order By: Relevance
“…One explanation could be that having recurrent and inadequately treated chest pain for a long time, without knowing the cause could lead to worries and depressive symptoms in NCCP and AP patients. 45,47 Regarding depressive symptoms in AMI patients, also previous research have reported high levels of depression the year after an AMI. 48,49 Study participants had a high number of contacts with health-care providers during the two year period, which also Leise and colleagues reported.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…One explanation could be that having recurrent and inadequately treated chest pain for a long time, without knowing the cause could lead to worries and depressive symptoms in NCCP and AP patients. 45,47 Regarding depressive symptoms in AMI patients, also previous research have reported high levels of depression the year after an AMI. 48,49 Study participants had a high number of contacts with health-care providers during the two year period, which also Leise and colleagues reported.…”
mentioning
confidence: 89%
“…43,44 Out of the 71 patients with depressive symptoms at baseline, more than half were still experiencing depressive symptoms at follow-up. Spalding and colleagues 45 reported that many patients were not diagnosed for more than a year, despite chest pain prevalence. This is probably due to the fact that formal screening for depression is not a part of the routine care for patients with chest pain and therefore depression can go unrecognized by cardiovascular physicians and nurses.…”
mentioning
confidence: 99%
“…Musculoskeletal chest pain accounts for many admissions to hospital, 8 and its natural history is poorly understood. 11 Serious pathologies including coronary artery disease can have similar symptom presentation to musculoskeletal chest pain, making a clear diagnosis challenging.…”
Section: Location Of Painmentioning
confidence: 99%
“…Undiagnosed chest pain patients on emergency medical admission are commonly discharged. 8 The absence of a firm diagnosis for chest pain can result in depression, anxiety, and a decrease in daily activity. 40 Such reactions have been ascribed directly to the absence of reassurance that symptoms do not indicate life-threatening disease.…”
Section: Location Of Painmentioning
confidence: 99%
See 1 more Smart Citation